Peripheral Nerve Focused Ultrasound Lesioning—Visualization and Assessment Using Diffusion Weighted Imaging - Walker, Matthew R.; Zhong, Jidan; Waspe, Adam C.; Piorkowska, Karolina; Nguyen, Lananh N.; Anastakis, Dimitri J.; Drake, James M.; Hodaie, Mojgan (Frontiers in neurology, 2021)
Objectives: Magnetic resonance-guided focused ultrasound (MRgFUS) is a non-invasive targeted tissue ablation technique that can be applied to the nervous system. Diffusion weighted imaging (DWI) can visualize and evaluate nervous system microstructure. Tractography algorithms can reconstruct fiber bundles which can be used for treatment navigation and diffusion tensor imaging (DTI) metrics permit the quantitative assessment of nerve microstructure in vivo . There is a need for imaging tools to aid in the visualization and quantitative assessment of treatment-related nerve changes in MRgFUS. We present a method of peripheral nerve tract reconstruction and use DTI metrics to evaluate the MRgFUS treatment effect. Materials and Methods: MRgFUS was applied bilaterally to the sciatic nerves in 6 piglets (12 nerves total). T1-weighted and diffusion images were acquired before and after treatment. Tensor-based and constrained spherical deconvolution (CSD) tractography algorithms were used to reconstruct the nerves. DTI metrics of fractional anisotropy (FA), and mean (MD), axial (AD), and radial diffusivities (RD) were measured to assess acute (<1–2 h) treatment effects. Temperature was measured in vivo via MR thermometry. Histological data was collected for lesion assessment. Results: The sciatic nerves were successfully reconstructed in all subjects. Tract disruption was observed after treatment using both CSD and tensor models. DTI metrics in the targeted nerve segments showed significantly decreased FA and increased MD, AD, and RD. Transducer output power was positively correlated with lesion volume and temperature and negatively correlated with MD, AD, and RD. No correlations were observed between FA and other measured parameters. Conclusions: DWI and tractography are effective tools for visualizing peripheral nerve segments for targeting in non-invasive surgical methods and for assessing the microstructural changes that occur following MRgFUS treatment.